2015
DOI: 10.1016/j.jtrangeo.2015.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Why live far? — Insights from modeling residential location choice in Bangladesh

Abstract: Increasing commute distances often lead to increased auto-dependency and is a major problem in many developed as well as developing countries. While in developed countries, the propensity to commute long distances generally originates from the preference to work in the core of the city and live in the suburb or periphery, in developing countries, the trend is often quite the opposite. For example, in Bangladesh, people generally have a strong preference to live at the heart of the major cities even if they wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 25 publications
0
8
0
3
Order By: Relevance
“…The review found the following. First, Choudhury and Ayaz () in a review of 45 studies that focus on commuting distance to workplace with relation to residential location as a deciding factor in whether a family moves or not, or migrates, found that most studies are concerned with metropolitan or urban areas in developed countries with few studies having been done in developing countries. Other studies in developed countries (Clark et al, ; Sandow, ; Shuttleworth and Gould, ; Shuai, ) also address this aspect of commuting, but as case studies in urban and peri‐urban areas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The review found the following. First, Choudhury and Ayaz () in a review of 45 studies that focus on commuting distance to workplace with relation to residential location as a deciding factor in whether a family moves or not, or migrates, found that most studies are concerned with metropolitan or urban areas in developed countries with few studies having been done in developing countries. Other studies in developed countries (Clark et al, ; Sandow, ; Shuttleworth and Gould, ; Shuai, ) also address this aspect of commuting, but as case studies in urban and peri‐urban areas.…”
Section: Introductionmentioning
confidence: 99%
“…As Choudhury and Ayaz () point out in their review, almost all studies of commuting patterns focus on developed countries. The literature search for this paper notes a further limitation of previous commuting studies, almost all, whether with a geographic focus of developed or developing countries, discuss commuting as it relates to suburban‐to‐urban, peri‐urban to urban, ex‐urban to urban, or rural‐to‐urban.…”
Section: Introductionmentioning
confidence: 99%
“…Others have assumed that housing market, dwelling characteristics and real estate values such as housing quality and pricing are endogenous to the choice process (e.g. Choudhury & Ayaz, 2015;Sermons & Koppelman, 1998;Kumarage, 2007;Cervero, 1998;Frenkel et al, 2013;Jun et al, 2013;Zhuge et al, 2016;Yi & Lee, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, numerous studies have explored the factors that affect residential location choice. Important determinants that influence housing choices include the characteristics of dwelling and neighbourhood, accessibility, socio-demographic characteristics, as well as an individual's lifestyle or preferences (latent factors) (Choudhury & Ayaz, 2015;Olaru, Smith, & Taplin, 2011;Tillema, van Wee, & Ettema, 2010). Travel preferences may also influence residential location decision.…”
Section: Background and Research Motivationmentioning
confidence: 99%
“…For instance, pensioners tend to choose environments that are quieter or close to relatives (Gobillon & Wolff, 2011), while young people who just graduated prefer to live closer to employment opportunities or city centres. Housing characteristics, such as house price, mortgage rates or rent cost (Choudhury & Ayaz, 2015;Olaru et al, 2011;Tillema et al, 2010), housing quality (Molin & Timmermans, 2003;Ozturk & Irwin, 2001), tenure type (Eluru et al, 2008;Frenkel, Bendit, & Kaplan, 2013), and the length of residency (Böheim & Taylor, 2002;Clark, 2013), also play a significant role in residential location choice. Some studies revealed that travel characteristics, such as car ownership (Cervero, 1998;Prashker, Shiftan, & Hershkovitch-Sarusi, 2008) and regular mode preferences (Abraham & Hunt, 1997;Pinjari, Pendyala, Bhat, & Waddell, 2011) have significant effects on housing choices as well.…”
Section: Socio-demographic Characteristicsmentioning
confidence: 99%